Interactive content on Instagram business profiles - Staletić, Nada; Štrbac-Savić , Svetlana; Jevremović , Milica (E-business technologies conference proceedings, 2021)
The further growth of popularity and influence of social media have left their mark in the last decade. Social media based on multimedia content exchange getting bigger and bigger users attention. According to the number of active users, Instagram today ranks 5th among global social media and it is the main promotion channel for all types of business. User behaviors research on Instagram shows that interactivity is one of the most significant social and psychological motives. This paper presents various forms of interactivity that are implemented in posts within the most popular Instagram formats - Stories, standard Feed posts and Live events. Next to that, the exposed interactive contents are analyzed from the aspect of achieving business goals, such as: e-shop sales; product promotion; raising brand awareness; generating potential buyers; collecting followers’ feedback and keeping customers.